Investigação de estratégias de controle de ordem fracionárias aplicadas a sistemas elétricos e industriais - AYRES JÚNIOR, Florindo Antonio de Carvalho (Universidade Federal do Pará, 2019)
The use of control techniques is of great importance to maintain competitive performance for electrical and industrial systems suitable to trace behavior adjustment points as close as possible to a desired set point of operation for deviation and oscillation reduced. In this work, fractional automatic control techniques are investigated to improve the performance of industrial systems. Two fractional-order control techniques are studied: one of the Lead-Lag based fractional order (FOLL) type based on the frequency response method and applied to the improvement of power system stabilizers (ESP). Control laws are implemented in the form of digital control in an embedded system, based on microcontroller. The performance of the compensators is evaluated by performing several experimental tests on a 10 kVA reduced scale power system located at the UFPA Electrical Engineering Laboratory. Variation tests are carried out at one pulse in the generator voltage reference at various power operation points of the micro generator system, in addition to the robustness analysis of the system using a robust plot tool from the Bode diagram known as RBode. Second, there is an investigation of a fractional pole allocation technique (FOPP) which takes into account temporal response criteria of fractional systems to three terms, which, in this work, are overtime, settlement time, applied in a coupled tanks system, and in a Buck DC / DC converter, where the FOPP technique is compared with two other techniques: these are the classical technique of integer pole allocation (IOPP), and a tuning technique of FOPID controllers based on Gain Margins and Phase Margins (GMPM). The results are corroborated by simulations in Matlab / Simulink Environment. The results show a reduction of approximately 15% at least in the ITAE and ISE indexes related to the dynamic performances of the systems addressed in this study associated with the controlled variable, with the insertion of the fractional controllers based on both the topology using the FOLL and using the FOPP and GMPM techniques, compared to the values obtained from these indexes of the controllers tuned by conventional whole order techniques.